Effect of Moringa oleifera Leaves Extract, Whey Protein, and Their Combination on Growth, Carcass and Meat Quality of Broiler Chickens - B. Ma'rifah; I. Agusetyaningsih; T. Sarjana; S. Kismiati; S. Sugiharto (Faculty of Animal Science, Bogor Agricultural University, 2023)
Restriction of synthetic antioxidants and prohibition of antibiotic growth promoters (AGP) have had an impact on impairing the growth rate of broiler chickens, and hence the alternatives for these additives are urgently needed by broiler farmers. The present study aimed to investigate the effect of Moringa oleifera leaves extract (MOLE), whey protein or their combination on the growth, carcass and meat quality of broilers. A total of 336 broiler chicks were arranged into four groups, including T0 (basal diet with no additive), T1 (basal diet with 1% MOLE), T2 (basal diet with 1% whey protein powder) and T3 (basal diet with 0.5% MOLE and 0.5% whey protein powder). Body weight and feed intake were recorded weekly. Internal organs and meats were obtained on day 42. Results showed that MOLE impaired body weight, body weight gain and feed conversion ratio of broilers (p<0.05). MOLE, whey protein and their blend decreased the abdominal fat content of broilers (p<0.05). Whey increased the moisture content of breast meats (p<0.05). Water holding capacity (WHC) was higher in T2 than in the other breast meats (p<0.05). Among the groups, pH value was highest in T2 breast meat (p<0.05). The lightness values of breast meat were lower in T2 than in the other groups (p<0.05), while the lowest yellowness values were found in T2 breast meat (p<0.05). The WHC was higher in T1 thigh meat than in T2 and T3 (p<0.05). The T1 thigh meat showed higher pH than the T2 group (p<0.05). The T1 thigh meat showed higher redness values than the other groups (p<0.05). In conclusion, MOLE reduced broiler growth and abdominal fat deposition. Whey reduced fat deposition and improved the meat quality of broilers.